Teaching elementary social studies : strategies, standards, and internet resources - Duplass, James A., 1947- (Boston : Houghton Mifflin Co., 2008)
Written for the elementary social studies methods course, this "interactive" program combines features of a textbook and a workbook, with thorough integration between the print text and a dynamic web site. Increasingly, majors in elementary education (if not the population at large) are more attuned to reading interactive material with relatively brief narrative, bulleted items, text boxes, and targeted messages (like web pages) rather than traditional, denser text. To accommodate these preferences, the layout of the print text features a larger-than-usual font, an 8 x 11" trim size, and spiral binding, and the content includes an abundance of bulleted lists, shaded text boxes, and contemporary graphics. The program's interactive approach and flexibility allow the professor to model the kinds of teaching principles and practices that students will want to use in their own elementary school classrooms. These principles and practices are integrated throughout the text and include a focus on active-learning strategies, application of constructivist principles, focus on Big Ideas and thinking skills, use of the Internet, and modeling of Best Practices and Performance-based assessments (based on INTASC and NCATE standard). Thus, the book will serve as a springboard for classroom activities, web site explorations, and/or instructor-led activities.
Introduction to Social Studies Fundamental Goals -- Planning Social Studies Instruction -- Assessing Student Learning in Social Studies -- Social Studies Disciplines, Standards, and Internet Resources -- Literacy and Basic Skills in Social Studies -- Social Studies Instructional Approaches -- Social Studies Methods -- List of Assignments and INTASC Standards Correlations
Spiral bound.
Includes bibliographical references (p. 365-371) and index.
1
Keywords: Social sciences -- Study and teaching (Elementary); Social Studies Fundamental Goals; Literacy and Basic Skills in Social Studies; Social Studies Instructional Approaches; Social Studies Methods; Assignments and INTASC Standards Correlations